Understanding the relationships between teacher mindfulness, work engagement, and classroom emotions - Tao, Wei (Frontiers in Psychology, 2022)
This cross-sectional study investigated the relationships between teacher mindfulness, work engagement and classroom emotions composed of positive and negative emotions. A sample of 498 Chinese primary, secondary and high school teachers completed an anonymous online questionnaire. Descriptive analysis, bivariate correlation and a series of regression equations were conducted to analyse the data. The results indicate that teacher mindfulness, work engagement and classroom emotions are all at the intermediate level, and significantly correlated. The effect of teacher mindfulness on classroom emotions is partially mediated by work engagement. In addition, negative emotions partially mediate the effect of teacher mindfulness on work engagement, while positive emotions fully mediate it. These results highlight the importance of fostering teacher mindfulness through mindfulness-based intervention, developing teacher emotion regulation competence in teacher education, and cultivating supportive classroom and school culture for teachers to experience more positive emotions from students and administrators.